Draft Annual Plan 2006-2007 Volume- II Annexures Planning & Development Department Government of Jharkhand Ranchi Government of Jharkhand - Planning Commission (Planning Commission, 2006)
DRAFT ANNUAL PLAN 2006-07 PROPOSED OUTLAYS, Proposed Outlay on Continuing and New Schemes, Physical Targets And Achievements, Statement Regarding Externally Aided Projects, Details of IEBR of SLPEs, Bharat Nirman Programmes, Districts Plan Outlays, Centrally Sponsored Schemes, Tribal Sub Plan (TSP): Financial Outlays, Tribal Sub Plan(TSP): Physical Targets
Planning & Development Department Government of Jharkhand Ranchi Government of Jharkhand